Effect of Umbilical Cord Milking on Morbidity and Survival in Extremely Low Gestational Age Neonates. Issue 4 (December 2015) - Patel, S.; Clark, E.A.S.; Rodriguez, C.E.; Metz, T.D.; Abbaszadeh, M.; Yoder, B.A.
Abstract : ( Am J Obstet Gynecol . 2014;211:519.e1–519.e7)